A defect in Δ(6 )and Δ(5 )desaturases may be a factor in the initiation and progression of insulin resistance, the metabolic syndrome and ischemic heart disease in South Asians - Das, Undurti N (BioMed Central, 2010)
The high incidence of insulin resistance and the metabolic syndrome in South Asians remains unexplained. I propose that a defect in the activity of Δ(6 )and Δ(5 )desaturases and consequent low plasma and tissue concentrations of polyunsaturated fatty acids such as γ-linolenic acid (GLA), dihomo-γ-linolenic acid (DGLA), arachidonic acid (AA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) and formation of their anti-inflammatory products prostaglandin E(1 )(PGE(1)), prostacyclin (PGI(2)), PGI(3), lipoxins, resolvins, protectins, maresins and nitrolipids could be responsible for the high incidence of insulin resistance, the metabolic syndrome and ischemic heart disease (IHD) in South Asians. This proposal is supported by the observation that South Asian Indians have lower plasma and tissue concentrations of GLA, DGLA, AA, EPA and DHA, the precursors of PGE(1), PGI(2), PGI(3), lipoxins, resolvins, protectins, and nitrolipids, the endogenous molecules that prevent platelet aggregation, vasoconstriction, thrombus formation, leukocyte activation and possess anti-inflammatory action and thus, are capable of preventing the development of insulin resistance, atherosclerosis, hypertension, type 2 diabetes mellitus and premature ischemic heart disease. Genetic predisposition, high carbohydrate intake, lack of exercise, tobacco use and low birth weight due to maternal malnutrition suppress the activity of Δ(6 )and Δ(5 )desaturases that leads to low plasma and tissue concentrations of polyunsaturated fatty acids and their products. This implies that adequate provision of polyunsaturated fatty acids and co-factors needed for their metabolism, and efforts to enhance the formation of their beneficial metabolites PGE(1), PGI(2), PGI(3), lipoxins, resolvins, protectins, maresins and nitrolipids could form a novel approach in the prevention and management of these diseases in this high-risk population.